Phase relations in ferroelectric/feffomagnetic TlInS2-TlCoS2 and TlGaSe2-TlCoSe2 systems - Seyidov, M. Yu.; Kerimova, E. M.; Veliyev, R. K.; Kerimov, R. N.; Mikailov, F. A. (Elsevier Science Sa, 2008)
Dielectric properties of TiInS2 and TIGaSe2 as well as magnetic properties of TICoS2 and TICoSe2 in the temperature interval of 77-400 K have been investigated and discussed. The results show that TlInS2 and TlGaSe2 exhibited ferroelectrics behavior, meanwhile TICoS2 and TICoSe2 exhibited ferrimagnetic-semimetal, and feriimagnetic-metal properties, respectively. On the base of these results the possibility of the coexistence of polar, and magnetic order in TlIn1-xCox,S-2 and TlGa1-xCoSe2 compounds has been proposed. The interaction in the quasi-binary systems TiInS2-TlCoS2 and TlGaSe2-TlCoSe2 has been studied, and the regions of homogeneous phases in these systems are revealed. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: chalcogenides; crystal growth; dielectric properties; ferroelectricity; magnetic properties